Smokers with chronic myeloid leukemia are at a higher risk of disease progression and premature death - Lauseker, Michael; Saußele, Susanne; Hehlmann, Rüdiger (Cancer, 2017)
Background: Smoking is suspected to not only be a risk factor for chronic myeloid leukemia but an adverse prognostic factor for the disease as well. The objective of the current study was to investigate the impact of smoking on survival and progression to advanced phases of disease. Methods: Based on the data of the German CML Study IV, the authors analyzed the effect of smoking using a multivariate Cox model with the addition of the European Treatment and Outcome Study (EUTOS) long-term survival score variables of age, spleen size, thrombocytes, and peripheral blasts as well as sex, comorbidities, and type of treatment center. Results: The 8-year survival probability was 87% for a nonsmoking patient and 83% for a patient who smoked. The authors noted a 2.08-times higher risk of death for smokers in comparison with nonsmokers and a 2.11-times higher cause-specific hazard of disease progression. An interaction between smoking and age was found in the model for survival. No significant difference with regard to molecular response was observed. Conclusions: Even when considering differences in socioeconomic status and lifestyle between patients who smoke and nonsmokers, the current analysis demonstrated that smoking also might affect disease biology. The results of the current study indicate that patients with chronic myeloid leukemia, in particular those aged <60 years, should be encouraged to quit smoking.